Impact of the COVID-19 epidemic on census, organization and activity of a large urban Emergency Department.: COVID-19 epidemic in a large Emergency Department - Comelli, Ivan; Scioscioli, Francesco; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2020)
Background. The spread of coronavirus disease 2019 (COVID-19) is overwhelming the response of many regional health services across Italy. This article aims to report and discuss the data of the first 8 weeks of COVID-19 epidemic in the emergency department (ED) of the University Hospital of Parma. Methods. The ED visits were analyzed as follows: total ED visits, divided in COVID-19/ non-COVID-19 cases, and in trauma-related/non-trauma-related cases; outcome (i.e., discharged, admitted, dead in the ED) of patients, altogether or stratified according to triage class; age classes of the entire ED population. Results. Total ED visits decreased starting from the first days of the outbreak, then exhibiting progressive growth afterwards. COVID suspected cases rapidly increased, whereas non-COVID suspected dropped and remained well below the standard. Trauma-related cases declined, both as ED visits and as hospital admissions. The percentage and absolute number of patients admitted to hospital wards progressively increased, rapidly overwhelming the number of cases that could be discharged. The admission rate in the lowest priority classes also displayed a marked increase. The youngest age classes dramatically declined, whilst the oldest progressively increased, remaining considerably over the standard rate of the local ED. Conclusions. The COVID-19 pandemic has obliged the health care systems to undergo a paradigm shift. Even triage criteria have partially lost their meaning, as shown by the dramatic increase of hospital admissions, even in the lowest priority classes. A deep re-organizational process of the ED was undertaken. Hospitals must be constantly resilient and prepared to these new emergencies in terms of equipment, medical and nurses staff, larger bed capacity in short time, availability of intensive and sub-intensive beds, and flexibility.